Assessing the Interchangeability of AVT02 and Humira® in Participants with Moderate-to-Severe Chronic Plaque Psoriasis: Pharmacokinetics, Efficacy, Safety, and Immunogenicity Results from a Multicenter, Double-Blind, Randomized, Parallel-Group Study - Feldman, S. R.; Kay, R.; Reznichenko, N. Yu.; Sobierska, J.; Dias, R.; Otto, H.; Haliduola, H. N.; Sattar, A.; Ruffieux, R.; Stroissnig, H.; Berti, F.; Резніченко, Наталія Юріївна (My University, 2023)
Background The US Food and Drug Administration (FDA) interchangeability guidelines state that the primary endpoint in a switching study should assess the impact of switching between the proposed interchangeable product and the reference product on clinical pharmacokinetics (PK) and pharmacodynamics (if available), as these assessments are generally sensitive to changes in immunogenicity and/or exposure that may arise due to switching. In addition, interchangeability designation requires no clinically meaningful difference in safety and efficacy of switching between the biosimilar and reference, compared with when using the reference product alone. Objectives The aim of this study was to investigate the PK, immunogenicity, efficacy, and safety in participants undergoing repeated switches between Humira ® and AVT02 as part of a global interchangeable development program. Methods This multicenter, randomized, double-blind, parallel-group study in patients with moderate-to-severe plaque psoriasis comprises three parts: lead-in period (weeks 1–12), switching module (weeks 12–28), and the optional extension phase (weeks 28–52). Following the lead-in period during which all participants received the reference product (80 mg in week 1, followed by 40 mg every other week), participants with a clinical response of ≥ 75% improvement in the Psoriasis Area and Severity Index (PASI75) were randomized 1:1 to receive AVT02 alternating with the reference product (switching arm) or reference product only (non-switching arm). At week 28, participants who were PASI50 responders could opt to take part in an open-label extension phase receiving AVT02 up to week 50, with an end of study visit at week 52. PK, safety, immunogenicity, and efficacy were evaluated at various timepoints throughout the study for both switching and non-switching arms. Results In total, 550 participants were randomized to switching (277) and non-switching arms (273). The switching versus non-switching arithmetic least square means ratio [90% confidence intervals (CIs)] was 101.7% (91.4–112.0%) for the area under the concentration–time curve over the dosing interval from weeks 26–28 (AUC tau, W26–28) and 108.1% (98.3–117.9%) for maximum concentration over the dosing interval from weeks 26–28 (Cmax, W26–28). The 90% CIs for the switching versus non-switching arithmetic means ratio for primary endpoints AUC tau, W26–28 and Cmax, W26–28 were within the prespecified limits of 80–125%, demonstrating comparable PK profiles between groups. In addition, the PASI, Dermatology Life Quality Index, and static Physician’s Global Assessment efficacy scores were highly similar for both treatment groups. There were no clinically meaningful differences between the immunogenicity and safety assessments of repeated switching between AVT02 and the reference product, versus the reference product alone.